The impact of air pollution from motor vehicles on public health: a comprehensive analysis - Mulia, Mimin Indriani; Lutpi, Nabilah Aminah (Environmental and Toxicology Management, 2024)
The presence of hazardous gas and particle emissions has a significant impact on human health. Therefore, a review is needed to analyze the impact of air pollution so that the public can be more aware of the importance of air pollution problems that occur around them. This review contains information related to the impact of air pollution collected from several previous studies that focus on air pollution and its impacts. The negative impacts on health caused by air pollution include lung disorders, heart disorders, immune system disorders, allergies, developmental disorders, cancer, and mental health disorders. The implementation of Environmental Tax, the use of corn cobs as activated carbon as an adsorbent, improving infrastructure and empowering mass transportation, and replacing BBM fuel with Hydrogen are some of the efforts that have been made to reduce air pollution due to gas emissions. In an effort to prevent the negative impacts of air pollution, consistency and commitment are needed from various sectors.